Maternal and Perinatal outcomes of oligohydramnios in a tertiary care hospital in Salem, Tamil Nadu, India - B., Jeyamani; J. P., Anurekha; J., Arun Daniel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Oligohydramnios is the term coined for a condition where the amount of liquor amnii is less than 200 ml at term. Using an ultrasonogram, oligohydramnios can be deliberated when the vertical pocket of liquor is less than 2 cm or when amniotic fluid index (AFI) is less than 5 cm. Oligohydramnios is reported to occur in 1 to 5% of total pregnancies. It has been associated with adverse maternal and foetal outcomes. Methods: This hospital-based follow-up study was conducted among 540 pregnant women at 37 weeks attending to the Department of Obstetrics and Gynaecology for a period of 1 year from January to December 2018. All included pregnant women were subjected to routine ultrasound examination and assessment of amniotic fluid volume using Amniotic fluid index. Results: The incidence of oligohydramnios was 17.04% (n=92) among the included women and 62% (n=57) among them were primigravida. Among those women diagnosed with Oligohydramnios, the caesarean section rate was 56.5% (n=52), the common indications for LSCS being fetal distress 44. 2% (n=23) and IUGR 34.6% (n=18). The oligohydramnios pregnancies had more associated post-dated deliveries (28.3%), pregnancy induced hypertension (10.9%) and gestational diabetes (8.7%). It was also associated with higher incidence of low birth weight (27.2%), NICU admissions (32.6%), congenital anomalies (3.3%) and fetal deaths (5.4%). Conclusions: The study showed that an amniotic fluid index of less than 5 at term was associated with adverse maternal and perinatal pregnancy outcomes emphasizing the importance of amniotic fluid volume surveillance during the antenatal period.